The (possible) effect of plain packaging on smoking prevalence in Australia: A trend analysis - Ashok Kaul; Michael Wolf (University of Zurich, Department of Economics, 2014)
A stated objective of the Australian Plain Packaging Act 2011 is to reduce smoking prevalence. We use the Roy Morgan Single Source (Australia) data set over the time period January 2001 to December 2013 to analyze whether this goal has been achieved in the first year since the implementation. In particular, we carry out a statistical trend analysis to study the (possible) effect of plain packaging on smoking prevalence. Two informative analyses help to draw conclusions on the (actual) effect of plain packaging on smoking prevalence in Australia. First, we look at the year of data before plain packaging was introduced, which happened in December 2012. Second, we compute confidence intervals around the estimated treatment effects. Our main results can be summarized as follows. First, if a statistical significance level of 5% is required, then there is no evidence at all for a plain packaging effect on smoking prevalence. Second, if one is willing to accept a relatively low level of statistical significance (that is, 10%), then there is evidence for a very short-lived plain packaging effect on smoking prevalence, namely in December 2012 only (after which smoking prevalence is statistically indistinguishable from its pre-existing trend). A formal power analysis demonstrates that the power of our inference methods is remarkably high.
Keywords: C13; C22; H43; I18; 330; Plain packaging; smoking prevalence; treatment effect; trend analysis